2017
DOI: 10.1007/s10792-017-0783-0
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructural alterations in the lens capsule and epithelium in eyes with traumatic white cataract

Abstract: The ultrastructural findings of our cases support that traumatically induced dysfunction of the lens epithelium may lead to an edema in superficial cortical lens fibers that subsequently undergo degeneration and produce a localized zone of vacuolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The clarity of the lens then progressively worsened with the duration of short-wavelength blue light exposure. The process of cataract formation illustrated in this study is consistent with that reported in an earlier study [35]. In this study, the phenotype is a cataract involving lens fiber cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The clarity of the lens then progressively worsened with the duration of short-wavelength blue light exposure. The process of cataract formation illustrated in this study is consistent with that reported in an earlier study [35]. In this study, the phenotype is a cataract involving lens fiber cells.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have confirmed that cumulative visible light exposure may accelerate the development of cataracts [ 34 ]. Dysfunction of the LECs may lead to superficial cortical lens fiber edema and mature cataracts [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It acts as an "optical windshield," which is exposed to not only longer wavelength ultraviolet (UV) radiation (300-400 nm) but also the full range of visible light (400-760 nm). When visible light passes through the cornea into the eye, it first comes in contact with the human lens epithelial cells (hLECs), cataract formation determined by this study is consistent with that determined by an earlier study 34 .…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we investigated the ultrastructure of aLC and LECs in HMC compared with ARC by TEM, to analyze the possible etiological mechanism of HMC. A lot of efforts have been devoted to explore the electron microscopic architecture of lens capsule since decades ago [6][7][8][9][10][11][12][13][14][15]. However, high-myopic cataracts haven't been involved so far.…”
Section: Discussionmentioning
confidence: 99%